Food quality vs food patriotism: Russian consumers' preferences for cheese after the food import ban. Issue 2 (4th February 2019) - Yormirzoev, Mirzobobo; Teuber, Ramona; Li, Tongzhe
Abstract : Purpose: The purpose of this paper is to investigate the role of perceived food quality and consumer ethnocentrism and potential trade-offs between these two concepts in Russian consumers' food purchase decisions after the implementation of the Russian import ban. Design/methodology/approach: Survey data were collected via in-person interviews in the City of Perm, which is one of the largest and most industrial cities in Russia. A double-bounded dichotomous-choice contingent valuation model is utilized to estimate willingness to pay (WTP) and to analyze factors that affect consumers' choice. Findings: The results suggest that most respondents do not consider domestically produced cheese as a risky product in terms of food safety but simply of lower quality than imported cheese. However, the average respondent's WTP discount for domestic cheese compared to imported cheese is 8 percent, which is relatively small. This corresponds to participants' opinion that buying domestic cheese is the right thing to do since it supports Russian farmers and producers. The results indicate further that with increasing education and income levels, individuals are less likely to prefer domestically produced cheese for either economic or quality reasons. This effect is stronger for the quality preference. Research limitations/implications: The results indicate that if the Russian government aims at expanding the domestic food market further, more attention needs to be paid to ensuring the quality of domestic food products in order to increase consumer acceptance and WTP. Originality/value: This is the first study providing empirical evidence on Russian consumers' attitudes and perceptions of domestically vs imported food products after the implementation of the Russian import ban, which can be considered as an external policy shock.